Spectral analysis of bent fiber Bragg gratings: theory and experiment - Lim, K.S.; Yang, H.Z.; Becir, A.; Lai, M.H.; Ali, M.M.; Qiao, X.G.; Ahmad, Harith (Optical Society of America, 2013)
This Letter presents a simple mathematical model developed from coupled-mode theory to describe the relationship between Bragg transmission loss (BTL), grating length, coupling coefficients, and bending loss in a bent fiber Bragg grating. In our investigation, the finding indicates that the decrement of BTL can be attributed to the increasing bending loss and degradation of both dc and ac coupling coefficients as the bending radius decreases. Besides, the center wavelength shifts as a result of coupling coefficients degradation. The validity of the proposed model is supported by experimental result.